A prospective study for the treatment of femur bone fracture following femur plate fixation with a screws to achieve initial stability and early mobilization - Rawat, Pooja; Kumar, Mohit; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2019)
Background: Fractures of the femur are relatively common, most often is caused by high-energy trauma in young and low-energy trauma in older persons. Femur fractures were classified according to Arbeitsgemeinschaft für Osteosynthesefragen system which included proximal, diaphyseal and distal. Methods: 30 patients prospective data was collected with a year of follow up. Clinical and radiological follow-ups were conducted at four weeks, twenty-four week, and forty-eight week after the discharge to check the bone union and implant-related complications. Three different plates were used for the treatment of fracture as per the fracture type (4.5/5.0 mm wise-lock distal femur plate, 4.5/5.0 mm wise-lock proximal femoral plate, 4.5/5.0 mm wise-lock proximal lateral femur plate (type II), 4.5/5.0mm wise-lock osteotomy medial distal femur plate). The patient's health status was evaluated by American Society of Anesthesiologists grade and the visual analog score (VSA) was also obtained. Results: The gradual decrease of the VSA score showed the results of the good significance related to pain management. The continued Physiotherapy under the supervisor of physiotherapists in all patients after discharge helps in good recovery and earlier mobilization. In the series of our 30 patients, no biomechanical complication was observed related to implant plate and screw-like loosening, bend, corrosion, etc. Conclusions: Femoral system (Auxein Medical Private Limited, India) is effective as a treatment for femur bone union. Definitive treatment of femur bone fracture fixation with Femoral System have good rate of success of mobilization and bone union in this study.